1995
DOI: 10.1007/bf00129006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of ethanol production by Saccharomyces cerevisiae from a glucose and maltose mixture

Abstract: A model for ethanol production from a glucose-maltose mixture has been proposed, which includes a term representing the glucose repression effect on maltose consumption. The model parameters were estimated from batch experimental data. Results of sensitivity analysis on the Monod constants for glucose and maltose, and the repression constant, showed that +10% changes in these three paraineters caused no significant effect on data fitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…All varieties in this study had similar productivity and yield to those obtained in other plants. However, the yield of the product relative to the substrate was lower (Y P/S ¼ 0.46 for BRS 508 and 0.463 for sugar cane juice) compared to the theoretical yield of 0.511 [39,40]. It is noteworthy that the species BR 508 showed a higher percentage of sucrose than the BR 506 and BR 509 and a higher percentage of glucose than the BR 511.…”
Section: Alcoholic Fermentation Of the Juice Of Sweet Sorghummentioning
confidence: 83%
“…All varieties in this study had similar productivity and yield to those obtained in other plants. However, the yield of the product relative to the substrate was lower (Y P/S ¼ 0.46 for BRS 508 and 0.463 for sugar cane juice) compared to the theoretical yield of 0.511 [39,40]. It is noteworthy that the species BR 508 showed a higher percentage of sucrose than the BR 506 and BR 509 and a higher percentage of glucose than the BR 511.…”
Section: Alcoholic Fermentation Of the Juice Of Sweet Sorghummentioning
confidence: 83%
“…So, we could think there was a complex regulation between the fermentation of glucose and maltose, and the starch hydrolysis. Refering to the literature [11], maltose consumption should be repressed by glucose but no paper had already described what interactions should exist between the sugar consumption, the fermentation and the starch hydrolysis. The ®rst study, before establishing the regulation process, was to describe the sugar pro®les during the SSF process.…”
Section: Resultsmentioning
confidence: 99%
“…These results corroborate the studies of Ernandes et al [12] who observed that maltose uptake will normally begin when approximately 50% of the initial glucose concentration in the wort has been taken up by the yeast, as a consequence of the glucose repression effect on maltose consumption. This repression effect has been con®rmed by using the Lee's model [11], and the sugar consumption is set up like this: glucose then maltose and ®nally maltotriose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach was employed by Lee et al [60] when they modeled the batch ethanol production by S. cerevisiae from a mixture of glucose and maltose. One term ξ was included in the equation of μ M to represent the glucose repression effect upon the maltose consumption.…”
Section: Eq (36) [48]mentioning
confidence: 99%